Research on property service mode innovation in the context of transformation and upgrading - Liu, Lijun; Zuo, Wenjin; Hu, Qiang; Zeng, Lanting (International Journal of Strategic Property Management, 2022)
Property service mode innovation is the basic means of property service enterprise management. Discussing the property service mode in terms of transformation and upgrading is of rich research significance, taking Wenzhou Sapphire Property Service Co. LTD. in China (hereafter referred to as “Sapphire Service”) as an example. First, based on the development of property service in China, this paper summarizes the 4E mode of traditional property service, ensuring cleaning, ensuring greening, ensuring maintenance and ensuring security, and analyzes the existing problems. Second, combined with the development needs of the property service industry, this paper proposes the 4R mode of modern property service, realizing quality requirements, realizing pleasure service, realizing social responsibility and realizing green health, and summarizes its basic characteristics. Finally, based on the above modes in the practice at Sapphire Service, some management implications are put forward for the industrial transformation and upgrading requirements.